The Role of the Navigator Person for a Patient with Lung Cancer - Smith, David E.; Raices, Micaela; Pollán, Javier A.; Pérez, Betiana M.; Grande Ratti, Maria Florencia (Revista del Hospital Italiano de Buenos Aires, 2023)
Introduction: Value-based medicine has succeeded in improving the quality of patient care and or patient satisfaction, reducing costs, and obtaining better outcomes. It rests on three fundamental pillars: evidence-based medicine, patient-centered care, and sustainability. However, there are few publications on the people navigator strategy for lung cancer patients, which could be a crucial tool for providing support, ensuring that they have access to the knowledge and resources needed to complete the recommended clinical care pathway.State of the art: It is a health intervention whose main objective is to overcome care-related barriers (e.g., logistical, bureaucratic-administrative, communication, and financial) to improve quality and access to health in the context of cancer care. These individuals play a guiding role for patients during the diagnostic and active treatment process. Their job is to link the patient with clinical providers, provide a support system, ensure individualized accompaniment, and guarantee that they get access to the knowledge and resources necessary to complete the appropriate follow-up and, or treatment.Discussion/Conclusion: Undoubtedly, patient navigators represent an increasingly recognized element of high-quality, patient-centered cancer programs. Its implementation will be of specific interest in the Integrated Practice Unit for people with lung cancer.
Keywords: integrated practice units; patient-reported outcomes; value-based healthcare; lung neoplasms